Phase equilibria in the CaO-La2O3-Nb2O5 system at 1823, 1773, and 1673 K. Issue 3 (2nd July 2020) - Qiu, Jiyu; Liu, Chengjun; Liu, Zhengyue; Zhu, Deying; Wang, Yeguang; Jiang, Maofa
ABSTRACT: Phase equilibria in the CaO-La2 O3 -Nb2 O5 system are of great significance for the utilization and application of rare earth and Nb resources. In the present work, the phase equilibria in high w (Nb2 O5 ) corner of the CaO-La2 O3 -Nb2 O5 system were studied by high-temperature equilibrium and quenching technology. Based on the continuity of phase diagram, a "Concavity and Convexity Rule" was proposed to predict the reasonable range of the unknown liquidus line. Finally, the isothermal sections and liquidus projection of the CaO-La2 O3 -Nb2 O5 phase diagram were constructed, which include the primary phase fields of CaNb2 O6, LaNbO4, Ca2 Nb2 O7, (Ca, Nb, La)O, and related liquidus lines at 1823, 1773, and 1673 K. Moreover, the subsolidus phase field of (Ca, Nb, La)O-LaNbO4 -Ca2 Nb2 O7 with peritectic nonvariant reaction and CaNb2 O6 -LaNbO4 -Ca2 Nb2 O7 with eutectic nonvariant reaction were determined, respectively.